COMBINED PATTERNS OF CONTROL HYDROBLOCKS - V. V. Pinchuk (Наука и техника)
When designing hydraulic drives the development of a control hydroblock is considered as the main part of this work. For simplifying the process of developing layouts of control hydroblocks, structural and hydraulic circuits of connective assembly unit should be presented as merged circuits, displaying its three-dimensional image.Graph synthesis of statement tasks pertaining to ultimate circuits and merged circuits of connective assembly unit allows to determine spatial arrangement of control hydroblock elements that simplifies the process of developing assembly hydroblock drawings.